Perancangan Media Pembelajaran Augmented Reality (AR) Pada Mata Pelajaran Kimia Menggunakan Unity di SMA Negeri 1 Bukittinggi - Irma, Widia; Okra, Riri; Musril, Hari Antoni; Derta, Sarwo (Jurnal Manajemen Informatika JAMIKA, 2024)
SMA Negeri 1 Bukittinggi is one of the educational institutions in Indonesia. At SMA Negeri 1 Bukittinggi there is an issue that learning activities are carried out using textbooks and PowerPoint slides as the main teaching tools. It was concluded from the results of interviews between researchers and several teachers at SMA Negeri 1 Bukittingi that the average learning media still uses conventional media. This is less effective in its application, especially in chemistry lessons which require special media that are more realistic, such as pictures of molecules and are easily visible inside and outside the classroom. Regarding this problem, research was carried out with the aim of designing Augmented Reality (AR) based chemistry learning media at SMA Negeri 1 Bukittinggi. Researchers use the Unity application as a media design tool. The aim of this research is to design Augmented Reality learning media using Unity at SMA N 1 Bukittinggi that is valid, practical and effective. Researchers use the Hannafin and Peck model as one of the development models for the SDLC method in this research. In the final stage, researchers used validity, practicality and effectiveness tests to draw conclusions about this research. The results of the effectiveness test from 34 students of class 4 validators got an average score of 0.85 (valid). This value test proves that the learning media that has been designed is useful and can be used in learning.